Combined transcriptomic and proteomic analysis reveals multiple pathways involved in self-pollen tube development and the potential roles of FviYABBY1 in self-incompatibility in Fragaria viridis - Du, Jianke; Ge, Chunfeng; Wang, Tao; Wang, Jing; Ni, Zhiyou; Xiao, Shiwei; Zhao, Fengli; Zhao, Mizhen; Qiao, Yushan (Frontiers in Plant Science, 2022)
Abstract: Fragaria viridis exhibits S-RNase-based gametophytic self-incompatibility, in which S-RNase is the major factor inhibiting pollen tube growth. However, the pathways involved in and the immediate causes of the inhibition of pollen tube growth remain unknown. Here, interactive RNA sequencing and proteome analysis revealed changes in the transcriptomic and proteomic profiles of F. viridis styles harvested at 0 and 24 h after self-pollination. A total of 2,181 differentially expressed genes and 200 differentially abundant proteins were identified during the pollen development stage of self-pollination. Differentially expressed genes and differentially abundant proteins associated with self-incompatible pollination were further mined, and multiple pathways were found to be involved. Interestingly, the expression pattern of the transcription factor FviYABBY1, which is linked to polar growth, differed from those of other genes within the same family. Specifically, FviYABBY1 expression was extremely high in pollen, and its expression trend in self-pollinated styles was consistent with that of S-RNase. Furthermore, FviYABBY1 interacted with S-RNase in a non-S haplotype way. Therefore, FviYABBY1 affects the expression of polar growth-related genes in self-pollen tubes and is positively regulated by S-RNase.